Cyfip1 Regulates SynGAP1 at Hippocampal Synapses - Sahasrabudhe, Abhishek; Begum, Fatema; Guevara, Christopher A.; Morrison, Chenel; Hsiao, Kuangfu; Kezunovic, Nebojsa; Bozdagi-Gunal, Ozlem; Benson, Deanna L. (Frontiers in Synaptic Neuroscience, 2021)
In humans, copy number variations in CYFIP1 appear to have sweeping physiological and structural consequences in the brain, either producing or altering the severity of intellectual disability, autism, and schizophrenia. Independently, SynGAP1 haploinsufficiency produces intellectual disability, and frequently, autism. Cyfip1 inhibits protein translation and promotes actin polymerization, and SynGAP1 is a synaptically localized Ras/Rap GAP. While these proteins are clearly distinct, studies investigating their functions in mice have shown that each regulates the maturation of synapses in hippocampus and haploinsufficiency for either produces an exaggerated form of mGluR-dependent long term depression, suggesting that some signaling pathways converge. In this study we examined how Cyfip1 haploinsufficiency impacts SynGAP1 levels and localization as well as potential sites for mechanistic interaction in mouse hippocampus. The data show that synaptic, but not total, levels of SynGAP1 in Cyfip1+/- mice were abnormally low during early postnatal development and in adults. This may be in response to a shift in the balance of kinases that activate SynGAP1, as levels of Cdk5 were reduced and those of activated CaMKII were maintained in Cyfip1+/- mice compared to wildtype mice. Alternatively, this could also reflect altered actin dynamics as Rac1 activity in Cyfip1+/- hippocampus was boosted significantly compared to wildtype mice, and levels of synaptic F-actin were generally increased, due in part to an increase in the activity of the WAVE regulatory complex. Decreased synaptic SynGAP1 coupled with a CaMKII-mediated bias toward Rap1 inactivation at synapses is also consistent with our data showing regional increases in levels of synaptic GluA2, increased AMPAR-mediated responses to stimulation, and increased levels of synaptic mGluR1/5 compared to wildtype mice. Collectively our data suggest that Cyfip1 regulates SynGAP1 and the two proteins work coordinately at synapses to appropriately direct actin polymerization and GAP activity.